As contribuições da música para o desenvolvimento e aprendizagem dos alunos do 6º ano do ensino fundamental II do Colégio Estadual Lavandeira-TO - Almeida, Jucilene Layara de (Universidade Federal do Tocantins, 2023)
The present research entitled “The contributions of music to the development and learning of 6th year students of Elementary School II at Colégio Estadual Lavandeira-TO” aims to identify how music can contribute to the teaching and learning process of students. It is understood that music education educates and disciplines. Its use in the school context of 6th grade students at Colégio Estadual Lavandeira is showing good results, as with the introduction of musical activities, students learn to listen and build new knowledge in a more active way, reflecting their artistic experiences through their imagination, skills and emotions. According to the law present in LDB no 9.394/96, the teaching of Arts must offer at least four artistic languages; theater, music, visual arts and dance. Art in its different languages has always been present in the life of humanity, but its importance has only been legally recognized in recent decades, as well as its proximity in the processes of artistic language and communication in the school space. Such insertion is supported by the importance that art has inside and outside the school for students, as well as its potential for their development. The methodology of this study is based on the perspective of bibliographic and documentary studies and to discuss the topic, studies by different authors and their respective understandings of the topic were used as theoretical support, including: Brescia, 2003, Gainza, 1988, Vygotsky, 1998, Candau, 2000, Forquin, 1993. The dialogues between the authors and documents point to the importance of art for humanity, justifying its insertion in the school space, mainly due to its interdisciplinary perspective, which gives the condition to work on contents in other areas of knowledge.